Advance in therapies targeting tumor-associated macrophages in ovarian cancer - Li, Man; Ma, Yue; Dai, Tinggeng; Wang, Yongxin; Yue, Ying (Frontiers in Immunology, 2025)
Ovarian cancer remains the deadliest gynecologic malignancy, with its aggressive progression and therapeutic resistance heavily influenced by the tumor microenvironment (TME). Tumor-associated macrophages (TAMs), the predominant immune infiltrates in OC, play pivotal roles in metastasis, immunosuppression, and chemoresistance by adopting a pro-tumoral M2 phenotype. Despite promising preclinical results, clinical translation faces challenges, such as on-target toxicity and incomplete understanding of TAM ontogeny in humans. This review summarizes the origins, heterogeneity, and functional plasticity of TAMs, emphasizing their mechanistic contributions to OC progression through epithelial-mesenchymal transition (EMT), angiogenesis, and immune evasion. We outline the emerging evidence that TAMs drive platinum resistance via exosomal signaling and metabolic reprogramming, underscoring TAMs as central mediators of OC pathogenesis and treatment paradigms.